pH-Dependent Mechanisms of Influenza Infection Mediated by Hemagglutinin - Caffrey, Michael; Lavie, Arnon (Frontiers in Molecular Biosciences, 2021)
Influenza hemagglutinin (HA) is a viral membrane bound protein that plays a critical role in the viral life cycle by mediating entry into target cells. HA exploits the lowering of the pH in the endosomal compartment to initiate a series of conformational changes that promote access of the viral genetic material to the cytoplasm, and hence viral replication. In this review we will first discuss what is known about the structural properties of HA as a function of pH. Next, we will discuss the dynamics and intermediate states of HA. We will then discuss the specific residues that are thought to be titrated by the change in pH and possible mechanisms for the pH triggered conformational changes. Finally, we will discuss small molecules that disrupt the pH trigger and thus serve as potential therapeutic strategies to prevent influenza infection.